RESERVOIR CHARACTERIZATION AND ESTIMATION OF CO2 STORAGE CAPACITY IN THE âSENOPATIâ FIELD, KUJUNG FORMATION, NORTH EAST JAVA BASIN - Fery Andriyansyah, Nanda
Indonesia is one of the countries that have committed to reducing greenhouse gas emissions. According to the Indonesia Center of Excellence Carbon Capture and Storage, the emission reduction target is set at 41% by 2030. One of the efforts to reduce greenhouse gas emissions is by developing and implementing CCS/CCUS technology. The “Senopati” field, which is a pilot project for implementing CCS/CCUS located in Pertamina Ep operating area, Central Java Province. The field has a direct CO2 content approximately 21% from total gas production. According to LEMIGAS in 2018, “Senopati” field is being used as a potential CO2 storage site. The study was conducted at depth interval of 2,730-3,570 m, Prupuh Member, Kujung Formation, North East Java Basin. The study aimed to study the geological structure of the area, obtain the relationship between facies and the distribution of petrophysical properties, and calculate the estimated gas reserves at the reservoir interval. The data used included well log data consisting of wells NFA-02, NFA-03, NFA-05, and NFA06, 3D seismic data, and biostratigraphic reports. The study consisted of several analyses, including well to seismic tie, horizon and fault, lithofacies, biostratigraphy, electrofacies, facies association, depositional environment, petrophysical analysis, CO2 storage capacity estimation, and gas reserve estimation at the study interval. The results of the analysis were obtained in succession, wavelet similarity with a resolution of 31-37 meters and 0.66 correlation coefficient. Horizons and faults were identified top and bottom Kujung Formation with the interpretation of a wrench fault oriented west – east, and a normal faults oriented northeast – southwest. Seven lithologies were identified based on Multi Resolution GraphedBased Clustering (MRGC), including mudstone, skeletal coral-clast wackestone, skeletal coral-clast packstone/grainstone, large benthic foram packstone/grainstone, foraminiferal wackestone, foraminiferal packstone, and coral boundstone. Facies association defined as basin margin, foreslope-basin margin, which was deposited in a carbonate rimmed platform with three sequence boundaries and parasequence sets of progradation and retrogradation. Petrophysical analysis produced an average of 0.27 shale volume, 0.1 effective porosity, and 0.32 water saturation. With the cutoff 0.4 for shale volume, o.o5 for effective porosity, and 0.7 for water saturation. The results of CO2 storage capacity estimation in confinement were divided into two areas (Area 1 ad Area 2), using P10, P50, and P90 efficiency factors. The values obtained in succession from Area 1 were 0.5 MMTCO2, 1.87 MMTCO2, 5.1 MMTCO2. In Area 2 were 1.72 MMTCO2, 6.45 MMTCO2, 17.64 MMTCO2. Based on the estimated gas hydrocarbon reserves, the values obtained were 131.6 BCF for Area 1, and 251.6 BCF for Area 2.